1996
DOI: 10.1093/carcin/17.5.1007
|View full text |Cite
|
Sign up to set email alerts
|

An aflatoxin-associated mutational hotspot at codon 249 in the p53 tumor suppressor gene occurs in hepatocellular carcinomas from Mexico

Abstract: The p53 tumor suppressor gene is commonly mutated in human hepatocellular carcinoma (HCC). The most frequent mutation in HCC in populations exposed to a high dietary intake of aflatoxin B1 (AFB1) is an AGGarg-->AGTser missense mutation in codon 249 of the p53 gene. We analyzed HCCs from Monterrey, Mexico, for the codon 249ser hotspot mutation. We also analyzed the serum AFB1-albumin adduct levels of the donors and family members to measure the current AFB1 exposure in this population. Moreover, the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 30 publications
2
73
0
5
Order By: Relevance
“…We first analyzed the mutational status of TP53 in these cell lines and identified in IST-MES 2 a p.Arg249Ser p53 mutation, which had never been described in mesothelioma. This mutation, lying in the DNAbinding domain, is considered an aflatoxin-associated mutational hotspot; 38 however, it remains to be established whether it could have a causal role in mesothelioma development. Then, we showed that both RITA and nutlin-3 are indeed able to increase p53 levels in mesothelioma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We first analyzed the mutational status of TP53 in these cell lines and identified in IST-MES 2 a p.Arg249Ser p53 mutation, which had never been described in mesothelioma. This mutation, lying in the DNAbinding domain, is considered an aflatoxin-associated mutational hotspot; 38 however, it remains to be established whether it could have a causal role in mesothelioma development. Then, we showed that both RITA and nutlin-3 are indeed able to increase p53 levels in mesothelioma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…DNA isolation for MSI has been described previously (18). A PCR-based approach (19) of microsatellite polymorphism analysis was used.…”
Section: Introductionmentioning
confidence: 99%
“…There is much data indicating that peanuts and corn are commonly contaminated with aflatoxin in China and other parts of the world. [15][16][17][18] In geographic areas with a high incidence of HCC, exposure to dietary aflatoxin B1 and chronic HBV infection are synergistic risk factors. 19,20 In this study, we found that there was a significant association between consumption of peanuts or corn and HCC.…”
Section: Discussionmentioning
confidence: 99%